Pengembangan Media Ular Tangga Berbantuan Augmented Reality untuk Meningkatkan Hasil Belajar Keberagaman Budaya Indonesia pada Siswa Kelas IV - Saadah, Syifa Nur; Bektiningsih, Kurniana (Universitas Muhammadiyah Magelang, 2026)
This study was motivated by the limited number of studies on the development of educational game-based learning media integrated with augmented reality technology in Pancasila Education, even though the use of innovative media has a significant impact on improving students’ learning outcomes and engagement. The purpose of this study was to develop and examine the feasibility and effectiveness of an augmented reality–assisted snakes and ladders learning media to improve learning outcomes on the topic of Indonesian cultural diversity among fourth-grade students at SDN Karangtengah Kaliwungu. The research employed a Research and Development (R&D) method using the ADDIE model, involving 19 students selected through purposive sampling. Data were collected using media expert and content expert validation sheets, teacher and student response questionnaires, as well as pretest and posttest instruments, and were analyzed using normality tests, paired sample t-tests, and N-Gain analysis. The results showed that the augmented reality–assisted snakes and ladders media was categorized as very feasible based on media expert validation with a score of 91.6% and content expert validation with a score of 92.5%, while the small-scale trial yielded feasibility scores of 88% from students and 98% from teachers, and the large-scale trial obtained a student response score of 90%. The effectiveness test indicated a significant improvement in learning outcomes, as evidenced by an increase in the average pretest score of 51.16 to a posttest score of 80.63, a paired sample t-test significance value of 0.000 (p < 0.05), and an N-Gain score of 0.60 classified as moderate. In conclusion, the augmented reality–assisted snakes and ladders learning media is feasible and moderately effective in improving elementary students’ learning outcomes on Indonesian cultural diversity, contributing theoretically to the enrichment of game-based learning and augmented reality media studies and practically providing teachers with an alternative for implementing more interactive and contextual Pancasila Education learning.